El surrealismo pictórico de René Magritte, como referente para una propuesta pictórica del paisaje rural del valle de casanga del cantón Paltas - Tandazo Mala, Ángel Daniel (2017)
The surrealist movement focuses its interest in the universe of objects, real, imbued with a symbolic and imaginative value, which tends to recreate objects possessing inspiration from which the artist interprets and expresses the subjective reality of being. In relation to the manifested the interest arises to carry out an investigation on "The pictorial surrealism of Rene Magritte, as reference for a pictorial proposal of the rural landscape of the valley of Casanga of the canton Paltas", the objective is to recognize the theoretical / esthetic foundations of the surrealism And relate it to the rural landscape of the Casanga valley. For the development of both the theoretical and practical part, the scientific, descriptive and inductive methods were used, which allowed the elaboration of the theoretical framework and in this way to base the pictorial proposal. In order to conclude the surrealist movement, it tries to portray the images of the deepest reality of the human being through symbolic abstract or figurative forms. Therefore Magritte's works offer the opportunity to recreate new works; In addition, the appropriation of works by other artists was necessary